2007
DOI: 10.1509/jppm.26.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Weathering the Storm: A Social Marketing Perspective on Disaster Preparedness and Response with Lessons from Hurricane Katrina

Abstract: The devastation of New Orleans as a result of Hurricane Katrina presents an opportunity and an obligation to examine the human and social factors that influenced the nation's response to this disaster. Lessons from Katrina suggest that a social marketing approach to disaster management could increase the likelihood of positive outcomes for individuals and communities when a disaster strikes. The authors propose an integrated approach to effective risk communications that encourages selfprotective behaviors.Dei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 21 publications
2
84
0
5
Order By: Relevance
“…Concerning receiver characteristics, studies have shown that, for instance, people with previous flood experience envisioned flood consequences differently compared to previously unaffected people: People without previous experience underestimated the negative effects of floods (Siegrist & Gutscher, 2008). This may have an effect on how they react to and follow for instance evacuation instructions, which is something that needs to be considered as it is important to affect and change people's behaviour before something happens and not whilst it is already going on (Guion, Scammon, & Borders, 2007). One possible way to do this is to make use of new socio-technical behaviour, and affect people through the use of social media (Goolsby, 2010).…”
Section: Environmental Cues and Receiver Characteristicsmentioning
confidence: 99%
“…Concerning receiver characteristics, studies have shown that, for instance, people with previous flood experience envisioned flood consequences differently compared to previously unaffected people: People without previous experience underestimated the negative effects of floods (Siegrist & Gutscher, 2008). This may have an effect on how they react to and follow for instance evacuation instructions, which is something that needs to be considered as it is important to affect and change people's behaviour before something happens and not whilst it is already going on (Guion, Scammon, & Borders, 2007). One possible way to do this is to make use of new socio-technical behaviour, and affect people through the use of social media (Goolsby, 2010).…”
Section: Environmental Cues and Receiver Characteristicsmentioning
confidence: 99%
“…For example, the model can interpret how a diabetes patient perceives long-term risks associated with unhealthy eating behaviors and whether such cognitive assessment may influence his/her diet habits accordingly. It was later justified by the scholars in behavioral studies concerning earthquake [22], wildfire [23], flooding [24], and other natural hazards [25], but the applications on slow-onset disasters are rare.…”
Section: The Linkages Between Risk Experience Perception and Mitigamentioning
confidence: 99%
“…Accelerated climate change due to human activities requires the rethinking of hazard risk management to incorporate the BCA approach. Traditional disaster management practice has four successive phases: mitigation, preparedness, response, and recovery [54]. The preparedness phase requires the consideration of a combination of adaptation strategies that are "no-regret" and cost-efficient.…”
Section: Integrating the Analysis Into Coastal Disaster Managementmentioning
confidence: 99%